PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DALAM PEMBELAJARAN PENDIDIKAN PANCASILA YANG BERDIFERENSIASI PADA SISWA KELAS V SD 54 PANGKAL PINANG - Fawwaz faqih al bakir; Rapinadia; Desti Olivia; Syaffa Putri Azzahra; Ririn Salsabina (STKIP Subang, 2026)
Pancasila education in primary schools currently faces serious challenges regarding the erosion of values ​​caused by unchecked exposure to digital popular culture. The core issue lies in the dominance of passive, conventional teaching methods, which fail to accommodate the diverse learning needs of students. This study examines the effectiveness of integrating the Problem-Based Learning (PBL) model within a differentiated learning framework as a pedagogical repositioning effort in a fifth-grade class at SD 54 Pangkal Pinang. Employing a descriptive qualitative method, the study maps changes in student interaction patterns when confronted with contextual moral dilemmas. Analysis reveals that providing flexible learning environments tailored to students' ability profiles optimizes cognitive engagement and deepens the internalization of Pancasila values. These findings underscore that the differentiated PBL model serves not merely as an instructional tool but also as a strategy for cultural preservation, fostering critical and adaptive character in students amidst an era of disruption. The study highlights the importance of strengthening teacher competence in designing learning scenarios that bridge the gap between the formal curriculum and the students' social realities..